A Binary Nature of the Marginal CP Star Sigma Sculptoris. (2nd April 2018) - Janík, Jan; Krtička, Jiří; Mikulášek, Zdeněk; Zverko, Juraj; Pintado, Olga; Paunzen, Ernst; Prvák, Milan; Skalický, Jan; Zejda, Miloslav; Adam, Christian
Abstract: The A2 V star σ Scl was suspected of being a low-amplitude rotating variable of the Ap-type star by several authors. Aiming to decide whether the star is a variable chemically peculiar (CP) star, we searched for the photometric and spectroscopic variability, and determined chemical abundances of σ Scl. The possible variability was tested using several types of periodograms applied to the photometry from Long-Term Photometry of Variables project (LTPV) and Hipparcos . Sixty spectrograms of high signal-to-noise (S/N) were obtained and used for chemical analysis of the stellar atmosphere and for looking for spectral variability that is symptomatic for the CP stars. We did not find any signs of the light variability or prominent chemical peculiarity, that is specific for the CP stars. The only exception is the abundance of scandium, which is significantly lower than the solar one and yttrium and barium, which are strongly overabundant. As a by-product of the analysis, and with the addition of 29 further spectra, we found that σ Scl is a single-lined spectroscopic binary with orbital period of 46.877(8) d. We argue that σ Scl is not an Ap star, but rather a marginal Am star in SB1 system. The spectral energy distribution of the binary reveals infrared excess due to circumstellar material.